(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: It’s important to include iodine for thyroid hormones to help you synthesize that needed for metabolism, brain development, and overall health. Iodine deficiency is a severe problem, especially in pregnant women, who have increased iodine requirements. It is important, but the knowledge of iodine deficiency and its consequences during pregnancy is very minimal in most of the populations which despite this fact this Saudi Arabia is no different. The objective of this study was to evaluate the knowledge and awareness on iodine deficiency, its risks, causes, complications during the reproductive or pregnancy period among women in Saudi Arabia. Methods: A descriptive cross-sectional survey was carried out from July to November 2024 among 1020 women aged 18 and above. A questionnaire including demographic and knowledge and practice on iodine consumption was completed by participants. The data were analyzed using Microsoft Excel and statistical significance by using SPSS. Results: Most participants (78.4%) identified iodine as essential micronutrient but 68.2% perceived their overall knowledge of iodine to be low. Although 60.4% were aware of iodine's teratogenic effects, misconceptions remained: 55.7% were of the opinion that adequate seafood consumption would replace iodized salt. In addition, more than half of participants (54.3%) did not list seafood as a key primary prevention against iodine deficiency. The association with age, education and gravidity but not with thyroid dysfunction history or current supplement use was significantly associated with awareness levels. Conclusion: Recognition of importance of iodine deficiency was a general, whilst these findings of the present study showed a gap in knowledge and awareness among women in Saudi Arabia. This emphasizes the need to address such an urgency in targeted educational interventions to enhance understanding of the role of iodine in maternal and fetal health and to subsequently minimize the risk of iodine deficiency during pregnancy. In future research, broader recruitment methods and longitudinal designs, for example, are explored so that knowledge mapping helps more clearly understand the link between knowledge and iodine status.